Combate ao crime organizado: um estudo do PCC e das instituições do sistema de justiça criminal - Freston, Rodrigo Braga (Universidade Federal de São Carlos, 2010)
The purpose of our research is to study the characteristics and actions of the group known as Primeiro Comando da Capital (PCC), in their relations with the institutions of the criminal justice system (police subsystem and criminal justice, execution, and administration), and the ramifications of the series of attacks perpetrated by that organization between May and August of 2006. At first, we give a theoretical analysis of the police apparatus and organized crime to, in turn, investigate the emergence, structure, activities, and objectives of PCC. We also focus on the series of attacks on these dates, on their effects on the criminal organization and, above all, on the public institutions who combat them. We compare these institutions evolution and the relationship between them, attempting to establish the degree to which the series of attacks became a catalyst for institutional change and in what way it allowed for a greater approximation between the institutions that are a part of this system.
Keywords: Crime organizado; Segurança pública; Polícia; Primeiro Comando da Capital; Sistema de Justiça Criminal; PCC; Police; Criminal Justice System; Organized crime; PCC; CIENCIAS HUMANAS::CIENCIA POLITICA